Chemical Composition, Antifeedant, Repellent, and Toxicity Activities of the Rhizomes of Galangal, Alpinia galanga Against Asian Subterranean Termites, Coptotermes gestroi and Coptotermes curvignathus (Isoptera: Rhinotermitidae). Issue 1 (16th February 2015) - Abdullah, Fauziah; Subramanian, Partiban; Ibrahim, Halijah; Abdul Malek, Sri Nurestri; Lee, Guan Serm; Hong, Sok Lai
Abstract : Dual choice bioassays were used to evaluate the antifeedant property of essential oil and methanolic extract of Alpinia galanga (L.) (locally known as lengkuas) against two species of termites, Coptotermes gestroi (Wasmann) and Coptotermes curvignathus (Holmgren) (Isoptera: Rhinotermitidae). A 4-cm-diameter paper disc treated with A. galanga essential oil and another treated with either methanol or hexane as control were placed in a petri dish with 10 termites. Mean consumption of paper discs (miligram) treated with 2, 000 ppm of essential oil by C. gestroi was 3.30 ± 0.24 mg and by C. curvignathus was 3.32 ± 0.24 mg. A. galanga essential oil showed significant difference in antifeedant effect, 2, 000 ppm of A. galanga essential oil was considered to be the optimum concentration that gave maximum antifeedant effect. The essential oil composition was determined using gas chromatography-mass spectrometry. The major component of the essential oil was 1, 8-cineol (61.9%). Antifeedant bioassay using 500 ppm of 1, 8-cineol showed significant reduction in paper consumption by both termite species. Thus, the bioactive agent in A . galangal essential oil causing antifeeding activity was identified as 1, 8-cineol. Repellent activity shows that 250 ppm of 1, 8-cineol caused 50.00 ± 4.47% repellency for C. gestroi, whereas for C. curvignathus 750 ppm of 1, 8-cineol was needed to cause similar repellent activity (56.67 ± 3.33%) . C. curvignathus is more susceptible compare to C. gestroi in Contact Toxicity study, the lethal dose (LD50 ) of C. curvignathus was 945 mg/kg, whereas LD50 value for C. gestroi was 1, 102 mg/kg. Hence 1, 8-cineol may be developed as an alternative control against termite in sustainable agriculture practices.